PENILAIAN ASPEK PERKEMBANGAN NILAI AGAMA DAN MORAL DI TK NEGERI PEMBINA 1 MEDAN - Fadhilah Salma Fauziah; Lulu Ilmaknun; Vivi Alaida Mahya; Cantika Putri Pores; Adinda Susanty Sitorus; Priska Melisa Panjaitan; Anita Yus; Artha Mahendra Diputra (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to explore the importance of developing religious and moral values from an early age in shaping good behavior and in accordance with prevailing values. Based on Piaget's theory, children's moral judgment and religious beliefs can be formed through two different processes, which depend on each individual's moral development. The research was conducted at TK Pembina 1 Medan on May 4, 2023 with 11 children in class B as research subjects, including Adypa, Alesha, Al-Ghazali, Azka Zein, Embun Hinata, Fathan, Jihan, Zevano, Raissa, and Valisa. There were 10 indicators of achievement identified, namely knowledge of the religion, modesty and politeness, honest behavior, wearing neat clothes, consumption of nutritious food, proper waste disposal, involvement in daily worship activities, diligence in listening to the teacher's explanation, saying greetings at the right time, saying thank you, asking permission when leaving the classroom, and apologizing when making mistakes. The results of this study provide a better understanding of the development of religious and moral values in early childhood and provide a foundation for the development of appropriate approaches and strategies in shaping positive behaviors in young children.